Measurement of Quality of Life II. From the Philosophy of Life to Science - Soren Ventegodt; Joav Merrick; Niels Jorgen Andersen (The Scientific World Journal)
We believe it should be possible to make operational the philosophical ideas of the good life in order to make it the object of scientific research. The Quality of Life Research Center in Copenhagen, Denmark has therefore spent the last several years with these questions and tried to find practical and evidence-based scientific solutions.This paper describes the theoretical road taken in moving from the abstract philosophy of life to the actual questionnaire. It presents an important aspect of our work with the quality-of-life (QOL) concept though the last decade. We have developed the quality-of-life philosophy; the SEQOL, QOL5, and QOL1 questionnaires; the quality-of-life theory; and the quality-of-life research methodology. We carried out quality-of-life population surveys and developed techniques for improving quality of life with the chronically sick patient. This paper presents the struggle to create a rating scale for the generic measurement of the global quality of life, based on quality-of-life theory, derived from quality-of-life philosophy. The developed rating scale is a ratio scale combining a Likert scale, a visual analogue scale, and a numerical scale, to a reduced combination scale. This allows for the extraction of as much information from the respondents as possible without exhausting them unduly or demanding more than can be reasonably expected.